Autonomous Self‐Healing Elastomers with Unprecedented Adhesion Force. (14th October 2020) - Zhang, Zhen; Ghezawi, Natasha; Li, Bingrui; Ge, Sirui; Zhao, Sheng; Saito, Tomonori; Hun, Diana; Cao, Peng‐Fei
Abstract: Self‐healable elastomers are extremely attractive due to their ability to prolong product lifetime. An additional function that could further expand their applications is strong adhesion force to clean and dusty surfaces. This study reports a series of autonomous self‐healable and highly adhesive elastomers (ASHA‐Elastomer) that are fabricated via a simple, efficient, and scalable process. The obtained elastomers exhibit outstanding mechanical properties with elongation at break up to 2102% and toughness (modulus of toughness) of 1.73 MJ m –3 . The damaged ASHA‐Elastomer can autonomously self‐heal with full recovery of functionalities, and the healing process is not affected by the presence of water. The elastomers are found to possess an ultrahigh adhesion force up to 3488 N m −1, greatly outperforming previously reported self‐healing adhesive elastomers. Furthermore, the adhesion force of the ASHA‐Elastomer is negligibly affected by dust on the surface, in stark contrast with regular adhesive polymers that have adhesion strengths extremely sensitive to dust. The successful development of high‐toughness, autonomous self‐healable, and ultra‐adhesive elastomers will enable a wide range of applications with enhanced longevity and versatility, including their use in sealants, adhesives, and stretchable devices. Abstract : A series of self‐healing adhesive elastomers are fabricated via a simple, efficient, and scalable process. The obtained elastomers exhibit outstanding mechanical properties (extensibility 2102%, toughness 1.73 MJ m –3 ), and the damaged areas can autonomously self‐heal with full recovery. They also possess an ultrahigh adhesion force (3488 N m −1 ), greatly exceeding the reported self‐healing adhesive elastomers.